Information Technology (IT) Projects – A Psychological Contract Perspective - Franco, Emilio (Université d'Ottawa / University of Ottawa, 2013)
Incorporating a psychological contract perspective into information technology projects, this study intends to explore the elements of the software publisher-reseller-end user psychological contract in the context of IT projects and contribute to existing literature in the field of IT psychological contracts. The data for this study was collected via 10 interviews conducted across 5 different cases. Interviewees were asked to describe IT projects they were recently involved in and outline what they perceived to be their obligations towards the other stakeholders and likewise, the obligations of the other stakeholders upon them. Interviews were transcribed and coded in accordance with existing IT project psychological contract elements derived from literature. The results of this study provided support to all psychological contract elements of the existing model and suggest refinements to better capture the perceived obligations of stakeholders in IT Projects. Furthermore, we observe that while the resellers’ and software publishers’ psychological contracts with end users conformed to the obligations expected under the model of supplier-customer relationships, the software reseller-software publisher psychological contracts reciprocally contained elements of both supplier and customer obligations. Finally, the findings of this study revealed that critical to the success of IT projects are the elements of transparency, accuracy, dedication, knowledge and responsibility.
Keywords: IT; Information technology; psychological contract; supply chain; software publisher; reseller; end user; customer; supplier; software; projects